THE RELATIONSHIP BETWEEN INDEPENDENCE LEARNING, PARENT’S ATTENTION, AND STUDENTS INTERACTION WITH TEACHER WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS XI TITL OF SMK NEGERI 1 PLERET BANTUL REGENCY - Betty Ria Hidayati; Suparyan Suparyan (Universitas Ahmad Dahlan, 2017)
Low student learning outcomes associated with many factors. The relationship between learning independence, parent’s attention and students interact with the teacher are some of the factors possibly related to learning outcomes. This research aims to determine the presence or absence of positive and significance the relationship between learning independence, parent’s attention and students interact with a teacher with Mathematics Learning Outcomes in Students Class XI TITL of SMK Negeri 1 Pleret Bantul Regency in the odd semester in the academic year of 2016/2017. The population in this research was the students of XI TITL grade in SMK Negeri 1 Pleret Bantul Regency in the academic year of 2016/2017, consisted of class XI TITLA, XI TITL B, and XI TITL C, totaling 94 students. Samples were taken from XI TITL A as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of learning independence, parent's attention and students interact with the teacher and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, the test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between learning independence, parent’s attention and students interact with teachers with mathematics learning outcomes in students class XI TITL in odd Semester of SMK Negeri 1 Pleret Bantul Regency in academic year of 2016/2017. It is showed by Fcount Ftable is with R = 0,8258 and R2 = 0,6820 with , with SR , SR and SR SE SE and SE .